Study and Analysis the effect of changing the distance between the elements of a (1x2) Patch Antenna Array on antenna performance - أحمد راما (Latakia University Journal -Engineering Sciences Series, 2025)
Microstrip patch antennas are the most widespread and widely used antennas due to their ease of manufacturing, light weight and small size, which makes them suitable for applications in wireless communications systems such as GPS, Wi-Fi, Bluetooth, satellite communications and medical applications. This research presents a model of a (1x2) array of inset-feed patch ​​antennas which connected to each other by a tree feed network with a distance r separating them. The array is on top of a FR4_epoxy substrate. The HFSS program was used to simulate the antenna array model and compare it with the single element model. The radiation patterns and scattering matrix S11 were obtained after verifying the convergence curves in the HFSS program to ensure accuracy in the results. It turns out that for a distance separating the centers of the two patches r =82mm, we obtain an antenna operating at the frequency of 2.43GHZ with a value of reflection coefficient S11=-41.16dB and bandwidth BW=102MHZ, and for a stand wave ratio VSWR<2 the antenna can operate on a very wide range of frequencies such as the X-band.